Mutation Analysis Approach to Develop Reliable Object-Oriented Software. (25th December 2014) - Sarma, Monalisa
Abstract : In general, modern programs are large and complex and it is essential that they should be highly reliable in applications. In order to develop highly reliable software, Java programming language developer provides a rich set of exceptions and exception handling mechanisms. Exception handling mechanisms are intended to help developers build robust programs. Given a program with exception handling constructs, for an effective testing, we are to detect whether all possible exceptions are raised and caught or not. However, complex exception handling constructs make it tedious to trace which exceptions are handled and where and which exceptions are passed on. In this paper, we address this problem and propose a mutation analysis approach to develop reliable object-oriented programs. We have applied a number of mutation operators to create a large set of mutant programs with different type of faults. We then generate test cases and test data to uncover exception related faults. The test suite so obtained is applied to the mutant programs measuring the mutation score and hence verifying whether mutant programs are effective or not. We have tested our approach with a number of case studies to substantiate the efficacy of the proposed mutation analysis technique.